Management of anterior thigh injuries in soccer players: practical guide - Lempainen Lasse; Mechó Sandra; Valle Xavier; Mazzoni Stefano; Villalon Jose; Freschi Marco; Stefanini Luca; García-Romero-Pérez Alvaro; Burova Maria; Pleshkov Pavel; Pruna Ricard; Pasta Giulio; et al. (BMC, 2022)
Most of the anterior thigh injuries are contusions or strains, however, some of these injuries can be career ending. Early diagnosis and correct treatment are key to successful outcome. Analyzing injury mechanism and adding both clinical and imaging findings, clinicians can make the right treatment decisions already often in the acute phase of the injury. Low grade contusions and muscle strains are treated well with planned rehabilitation, but complete tendon injuries or avulsions can require operative treatment. Also, neglected minor injuries could lead to chronic disabilities and time lost from play. Typical clinical presentation of anterior thigh injury is swelling and pain during hip flexion or knee extension. In more severe cases a clear gap can be palpated. Imaging methods used are ultrasound and magnetic resonance imaging (MRI) which are helpful for clinicians to determine more exact the extent of injury. MRI can identify possible tendon retractions which may need surgery. Clinicians should also be aware of other traumatic lesions affecting anterior thigh area such as myositis ossificans formation. Optimal treatment should be coordinated including acute phase treatment with rest, ice, and compression together with designed return-to-play protocol. The anatomical structure involved lines the treatment pathway. This narrative review describes these more common reasons for outpatient clinical visits for anterior thigh pain and injuries among soccer players.